DEVELOPMENT OF QUICK RETURN MECHANISM FOR EXPERIMENTATION USING SOLIDWORKS - NURUDEEN OLATUNDE ADEKUNLE; KOLAWOLE ADESOLA OLADEJO; ISMAILA OLASUNKANMI SALAMI; ADEWALE OREOLUWA ALABI (Journal of Engineering Studies and Research)
Quick Return Mechanisms (QRMs) are one of the essential accessories used in machine tools which involve reciprocating cutting action with a quick return stroke and a constant angular velocity of driving crank. The aim of this work was to simulate, design and construct a prototype of a QRM that can be used for demonstration and instrumentation. The QRM was simulated using Solidworks and a prototype was developed from the simulated results. The experiment was conducted using the prototype. The kinematic simulation of the Solidworks model was compared with the kinematics of motion of the prototype. The result showed that the Percentage Stroke Length error was 0.36%. It was observed that, there was no significant difference in the simulated and experimental results, hence, the prototype can be used for demonstration and experimentation to assist students in understanding basic principles of the machine operation.